Another way to successfully remove dialysis catheter misplaced into subclavian artery through right internal jugular vein: case report - Li, Xiaodong; Yancong Guo (Journal of the Pakistan Medical Association, 2023)
For haemodialysis in patients with uraemia, catheterization of the internal jugular or femoral vein is often required to establish access. Puncture with catheterization in the right internal jugular vein (RIJV) is relatively simple, and thus, is the appropriate choice for haemodialysis. However, catheterization at this site can lead to complications, including bleeding at the puncture site. Moreover, in several cases, the haemodialysis catheter (HDC) can be misplaced in the internal carotid artery and subclavian artery, thus making the management troublesome later on. In this article, we report the case of a middle-aged female patient with uraemia wherein a temporal HDC was misplaced into the right subclavian artery during right internal jugular vein catheterization. Instead of conventional surgery and endovascular intervention, the catheter was left in that place for four weeks and subsequently removed directly, followed by local compression for 24 hours. —Continue